2018
DOI: 10.1097/mnm.0000000000000850
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-18-fluorocholine PET/CT parameters predictive for hematological toxicity to radium-223 therapy in castrate-resistant prostate cancer patients with bone metastases

Abstract: PurposeThis study aims to predict hematological toxicity induced by 223Ra therapy. We investigated the value of metabolically active bone tumor volume (MBTV) and total bone lesion activity (TLA) calculated on pretreatment fluorine-18-fluorocholine (18F-FCH) PET/CT in castrate-resistant prostate cancer (CRPC) patients with bone metastases treated with 223Ra radionuclide therapy.Patients and methods18F-FCH PET/CT imaging was performed in 15 patients with CRPC before treatment with 223Ra. Bone metastatic disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In addition, the cell membrane phospholipid choline can be abnormally metabolized and internalized in tumor cells overexpressing choline kinase (352). This abnormal regulation of the phospholipid metabolism has been observed in situ in cancer cells metastatic to bone (290,348), as visualized by FCH-PET scanning of prostate cancer bone metastases (Figure 8). Autophagy could be another potential source of energy for tumor cells in bone (233).…”
Section: Fueling Expansion -Reprogramming Energy Metabolism To Facilitate Bone Metastasis Progressionmentioning
confidence: 85%
“…In addition, the cell membrane phospholipid choline can be abnormally metabolized and internalized in tumor cells overexpressing choline kinase (352). This abnormal regulation of the phospholipid metabolism has been observed in situ in cancer cells metastatic to bone (290,348), as visualized by FCH-PET scanning of prostate cancer bone metastases (Figure 8). Autophagy could be another potential source of energy for tumor cells in bone (233).…”
Section: Fueling Expansion -Reprogramming Energy Metabolism To Facilitate Bone Metastasis Progressionmentioning
confidence: 85%
“…Pre-treatment PET imaging has served as a primary research focus to identify patients who would benefit from or fail therapies with various radionuclide and targeting moiety combinations. For example, Vija et al demonstrated that quantification of bone tumoural burden using 18F-Fluoromethylcholine ( 18 F-FCH) PET/CT could predict normal tissue toxicity, specifically grade 2–3 haematological toxicity after 223 Ra therapy [1]. For tumour response, Murray et al showed that if the response is defined as a change of >21% in the mean standard uptake value (SUV mean ) of bone lesions, the percentage change of 18 F-fluoride PET SUV mean relative to baseline could identify non-responding bone lesions prior to 223 Ra therapy (r 2 = 0.77) [2].…”
Section: Developments In Individualisation Of Treatmentmentioning
confidence: 99%
“…These tracers do not actively target haematological cells, but the circulation phase and accumulation in normal bone or bone metastases can result in significant dose to bone marrow [41]. A study used baseline [ 18 F]fluorocholine(FCH) PET, typically used to detect metastatic recurrent prostate cancer, to determine bone tumour infiltration and was thereby able to predict haematological toxicity in metastatic prostate cancer patients who received 223 Ra therapy [42]. Imaging the normal tissue directly with [ 18 F]FLT-PET could possibly be used to evaluate toxicity in these cases as well.…”
Section: Bone Marrowmentioning
confidence: 99%